Ejercicio 90

Comparte esto 👍👍
CAPITULO X

Descomposición Factorial
Ejercicio 90
Factorar o descomponer en dos factores:
  1. a(x+1 ) +b(x+1 ) =(x+1 ) (a+b )
  2. x(a+1 ) 3(a+1 ) =(a+1 ) (x3 )
  3. 2(x1 ) +y(x1 ) =(x1 ) (2+y )
  4. m(ab ) +(ab ) n=(ab ) (m+n )
  5. 2x(n1 ) 3y(n1 ) =(n1 ) (2x3y )
  6. a(n+2 ) +n+2 =a(n+2 ) +(n+2 ) =(n+2 ) (a+1 )
  7. x(a+1 ) a1 =x(a+1 ) (a+1 ) =(a+1 ) (x1 )
  8. a 2 +1b( a 2 +1 ) =( a 2 +1 ) b( a 2 +1 ) ( a 2 +1 ) (1b )
  9. 3x(x2 ) 2y(x2 ) =(x2 ) (3x2y )
  10. 1x+2a(1x ) =(1x ) +2a(1x ) =(1x ) (1+2a )
  11. 4x(mn ) +nm =4x(mn ) m+n =4x(mn ) (mn ) =(mn ) (4x1 )
  12. mn+x(m+n ) =(m+n ) +x(m+n ) =(m+n ) (x1 )
  13. a 3 (ab+1 ) b 2 (ab+1 ) =(ab+1 ) ( a 3 b 2 )
  14. 4m( a 2 +x1 ) +3n(x1+ a 2 ) =4m(x1+ a 2 ) +3n(x1+ a 2 ) =(x1+ a 2 ) (4m+3n )
  15. x(2a+b+c ) 2abc =x(2a+b+c ) (2a+b+c ) =(2a+b+c ) (x1 )
  16. (x+y ) (n+1 ) 3(n+1 ) =(n+1 ) [(x+y ) 3 ] =(n+1 ) (x+y3 )
  17. (x+1 ) (x2 ) +3y(x2 ) =(x2 ) [(x+1 ) +3y ] =(x2 ) (x+3y+1 )
  18. (a+3 ) (a+1 ) 4(a+1 ) =(a+1 ) [(a+3 ) 4 ] =(a+1 ) (a1 )
  19. ( x 2 +2 ) (mn ) +2(mn ) =(mn ) [( x 2 +2 ) +2 ] =(mn ) ( x 2 +2+2 ) =(mn ) ( x 2 +4 )
  20. a(x1 ) (a+2 ) (x1 ) =(x1 ) [a(a+2 ) ] =(x1 ) ( a a 2 ) =2(x1 ) =2(1x )
  21. 5x( a 2 +1 ) +(x+1 ) ( a 2 +1 ) =( a 2 +1 ) [5x+(x+1 ) ] =( a 2 +1 ) (6x+1 )
  22. (a+b ) (ab ) (ab ) (ab ) =(a+b ) (ab ) (ab ) 2 =(ab ) [(a+b ) (ab ) ] =(ab ) ( a +b a +b ) =2b(ab )
  23. (m+n ) (a2 ) +(mn ) (a2 ) =(a2 ) [(m+n ) +(mn ) ] =(a2 ) (m+ n +m n ) =2m(a2 )
  24. (x+m ) (x+1 ) (x+1 ) (xn ) =(x+1 ) [(x+m ) (xn ) ] =(x+1 ) ( x +m x +n ) =(x+1 ) (m+n )
  25. (x3 ) (x4 ) +(x3 ) (x+4 ) =(x3 ) [(x4 ) +(x+4 ) ] =(x3 ) (x 4 +x+ 4 ) =2x(x3 )
  26. (a+b1 ) ( a 2 +1 ) a 2 1 =(a+b1 ) ( a 2 +1 ) ( a 2 +1 ) =( a 2 +1 ) [(a+b1 ) 1 ] =( a 2 +1 ) (a+b2 )
  27. (a+bc ) (x3 ) (bca ) (x3 ) =(x3 ) [(a+bc ) (bca ) ] =(x3 ) [a+ b c b + c +a ] =2a(x3 )
  28. 3x(x1 ) 2y(x1 ) +z(x1 ) =(x1 ) (3x2y+z )
  29. a(n+1 ) b(n+1 ) n1 =a(n+1 ) b(n+1 ) (n+1 ) =(n+1 ) (ab1 )
  30. x(a+2 ) a2+3(a+2 ) =x(a+2 ) (a+2 ) +3(a+2 ) =(a+2 ) (x1+3 ) =(a+2 ) (x+2 )
  31. (1+3a ) (x+1 ) 2a(x+1 ) +3(x+1 ) =(x+1 ) [(1+3a ) 2a+3 ] =(x+1 ) (1+3a2a+3 ) =(x+1 ) (a+4 )
  32. (3x+2 ) (x+yz ) (3x+2 ) (x+y1 ) (3x+2 ) =(3x+2 ) [(x+yz ) 1(x+y1 ) ] =(3x+2 ) [ x + y z 1 x y + 1 ] =z(3x+2 )